2013
DOI: 10.18632/oncotarget.1234
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction-resistant human tumors harboring the PIK3CA-activating mutation H1047R are sensitive to metformin

Abstract: ABSTRACT:Cancer cells expressing constitutively active phosphatidylinositol-3 kinase (PI3K) are proliferative regardless of the absence of insulin, and they form dietary restriction (DR)-resistant tumors in vivo. Because the binding of insulin to its receptors activates the PI3K/AKT/mammalian target of rapamycin (mTOR) signaling cascade, activating mutations in the PIK3CA oncogene may determine tumor response to DRlike pharmacological strategies targeting the insulin and mTOR pathways. The antidiabetic drug me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…The mechanisms involved in the antineoplastic effects of metformin are probably very diverse, including activation of adenosine monophosphate kinase (AMPK) [12], phosphatidylinositol-3 kinase (PI3K) mutation [13], p53 deficiency [14] and so on. Among these mechanisms, the AMPK- mammalian target of rapamycin (mTOR) axis plays a central role for the antineoplastic effects of metformin.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in the antineoplastic effects of metformin are probably very diverse, including activation of adenosine monophosphate kinase (AMPK) [12], phosphatidylinositol-3 kinase (PI3K) mutation [13], p53 deficiency [14] and so on. Among these mechanisms, the AMPK- mammalian target of rapamycin (mTOR) axis plays a central role for the antineoplastic effects of metformin.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have shown that metformin can negatively affect the growth of human tumors even in the presence of activating mutations in the PIK3CA oncogene, another evolutionary conserved regulator of cell metabolism that converges with and impinges on the mTOR pathway. 10,[26][27][28][29][30][31][32][33][34][35][36][37] To anticipate the potential mechanisms of acquired resistance to metformin during the course of treatment, we recently established metformin-resistant pooled cell populations from the MCF-7 breast carcinoma cell line. Thus, to assess what impact the resistance phenomenon might have on metforminbased therapies, genome-wide analyses using Agilent 44K Whole Human Genome Arrays were evaluated using a bioinformatics approach with the ingenuity pathway analysis (IPA) software.…”
mentioning
confidence: 99%
“…Conversely, if we assume the real possibility that the antitumoral activity of metformin can be attributed to its many direct actions on target cancer cells as shown in vitro , we should then consider that, in certain contexts, short-term exposure to higher doses of biguanides could have clinical use in oncology. Thus, in addition to the fact that particular tissues known to accumulate relatively high metformin levels following conventional oral dosing ( e.g., liver, gastrointestinal tract) may provide proof-of-concept clinical models for investigation of the occurrence and relevance of metformin's direct mechanisms of action ( e.g., reduction of hepatoma risk, prevention of familial or sporadic intestinal polyposis) [7], we should contemplate the utility of other unconventional routes of short-term high-dose metformin exposure alone and in combination regimens. As for the above-mentioned case of MTX, we here propose that “oncobiguanides” should be viewed as a different type of anti-cancer drugs when employed at doses notably higher than those used chronically when operating as “diabetobiguanides”.…”
mentioning
confidence: 99%
“…Moreover, the actual relevance of measuring the circulating levels of metformin in predicting the risk of lactic acidosis remains unclear. Additionally, although there is uncertainty concerning the feasibility of administering biguanides through non-conventional routes to investigate the therapeutic value of high-dose transient exposure, we should acknowledge that biguanides have a better safety profile than most oncology drugs in current use [7]. Perhaps it is time to consider that, as with any drug, there is a metformin dose range that is without any effect, one corresponding to “diabetobiguanides” with a pharmacological effect ( e.g., insulin sensitization in type 2 diabetes, prevention of insulin-dependent carcinogenesis, indirect inhibition of insulin- and growth factor-dependent cancer growth) but with minimal toxicity and another corresponding to “oncobiguanides” with pharmacological ( i.e., direct and strong anti-cancer activity) as well as toxic effects (Fig.…”
mentioning
confidence: 99%